Foliar Phenolic Compounds in Norway Spruce with Varying Susceptibility to Chrysomyxa rhododendri: Analyses of Seasonal and Infection-Induced Accumulation Patterns - Ganthaler, Andrea; Stöggl, Wolfgang; Kranner, Ilse; Mayr, Stefan (Frontiers in Plant Science, 2017)
Secondary phenolic metabolites are involved in plant responses to various biotic stress factors, and are apparently important for the defense against fungal pathogens. In this study, we investigated their role in defense against the rust Chrysomyxa rhododendri in Norway spruce. The fungal pathogen undergoes a seasonal lifecycle with host shift; after overwintering in rhododendron shrubs, it attacks the sprouting current-year spruce needles and causes needle fall in autumn. Repeated infections lead to reduced timber yield and severe problems with rejuvenation in subalpine Norway spruce forests. Trees with varying susceptibility to infection by C. rhododendri were selected and foliar phenolic composition was assessed using UHPLC-MS. We report on seasonal accumulation patterns and infection-related changes in the concentrations of 16 metabolites, including flavonoids, stilbenes, simple phenylpropanoids and the precursor shikimic acid, and their correlation with the infection degree of the tree. We found significant variation in the phenolic profiles during needle development: flavonoids were predominant in the first weeks after sprouting, whereas stilbenes, picein and shikimic acid increased during the first year. Following infection, several flavonoids and resveratrol increased up to 1.8 fold in concentration, whereas picein and shikimic acid were reduced by about 70 and 60%, respectively. The constitutive and early stage infection-induced concentrations of kaempferol, quercetin and taxifolin as well as the late stage infection-induced concentrations of stilbenes and picein were negatively correlated with infection degree. We conclude that a combination of constitutive and inducible accumulation of phenolic compounds is associated with the lower susceptibility of individual trees to C. rhododendri. The potentially fungicidal flavonoid aglycones may limit hyphal growth and prevent development of infection symptoms, and high levels of stilbenes may impede the infection of older needles. The presented results underline a highly compound-specific seasonal accumulation and defense response of Norway spruce and may facilitate the selection of promising trees for breeding programs.